2019
DOI: 10.1029/2018gb006113
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Iron Supply from Asian Glaciers: Local Controls and a Regional Perspective

Abstract: Ice sheets have been shown to deliver large amounts of labile iron (Fe) to aquatic ecosystems; however, the role of glaciers distinct from ice sheets in supplying labile Fe to downstream ecosystems is less well understood despite their rapid volume loss globally. Direct and continuous measurements of Fe from glaciers throughout an entire melt season are very limited to date. Here we present extensive seasonal data on 0.45‐μm‐filtered Fe (dFe) from three glaciers in Asia. Concentrations of dFe are negatively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…The results of the AFeR extractions are consistent with differences in Fe-mineralogical composition detected by 57 Fe Mössbauer spectroscopy, showing that iron in a Kongsfjorden plume sample had a relative abundance of 17.8±1.6% hematite, whereas material from a Kongsfjorden iceberg contained about twice as much hematite, accounting for 41.3±1.9% of the iron pool ( Figure S1, Table S2). These data corroborate results of Raiswell and coworkers 18 , who showed that FeR produced by chemical and biological weathering in subglacial systems 18,52,53 gets slowly converted into less reactive phases such as goethite or hematite in glacial ice, which may explain the higher proportion of hematite found in the icebergs. Given the low amount of FeR in the glacial sources, only a small fraction (0.6-12%) of glacially derived iron is immediately available for microbial reduction in the sediment 26 and potentially bioavailable for phytoplankton 23 .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the AFeR extractions are consistent with differences in Fe-mineralogical composition detected by 57 Fe Mössbauer spectroscopy, showing that iron in a Kongsfjorden plume sample had a relative abundance of 17.8±1.6% hematite, whereas material from a Kongsfjorden iceberg contained about twice as much hematite, accounting for 41.3±1.9% of the iron pool ( Figure S1, Table S2). These data corroborate results of Raiswell and coworkers 18 , who showed that FeR produced by chemical and biological weathering in subglacial systems 18,52,53 gets slowly converted into less reactive phases such as goethite or hematite in glacial ice, which may explain the higher proportion of hematite found in the icebergs. Given the low amount of FeR in the glacial sources, only a small fraction (0.6-12%) of glacially derived iron is immediately available for microbial reduction in the sediment 26 and potentially bioavailable for phytoplankton 23 .…”
Section: Resultssupporting
confidence: 91%
“…The majority of glacially-derived iron is in the particulate form or will rapidly become particulate once in contact with oxic and saline fjord water due to oxidation and flocculation reactions 15-20 , resulting in up to 95% of glacially-sourced iron settling to fjord sediments after entering the marine environment. However, the amount and physical and chemical characteristics of glacial iron that is delivered to Arctic fjords, as well as its fate, remain poorly constrained 12,21 . Speciation, particle size, surface area, and crystallinity are physical and chemical characteristics of iron minerals that determine if it is available for biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Filterable Fe concentrations are highest from glacial systems in Peru, Alaska, the Alps, and Patagonia, all of which have concentrations more than an order of magnitude higher than mean global riverine values (0.48 μM; Gaillardet et al, 2014). Such high Fe concentrations highlight that glacial systems are important components of the Fe cycle and that further research is needed to understand how Fe cycling will change in a warming world (Li et al, 2019). However, as discussed previously, details of the mineralogy, phase‐speciation and estuarine transformations are critical to determining the lability and impacts of CNFe in downstream ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…Filterable Fe concentrations have also been studied for some mountain glacial systems, with concentrations and yields exceeding those from the Greenland Ice Sheet (Li et al, 2019;Schroth et al, 2011). However, Fe exports from glacial systems are highly variable, and there are still many critical unknowns regarding the factors controlling Fe production, the bioavailability of different phases, exchange between fjord and coastal waters, and how glacial nutrient exports are likely to change in the future (Hawkings et al, 2018;Hopwood et al, 2015;Li et al, 2019;Raiswell et al, 2018;Schroth et al, 2011Schroth et al, , 2014.…”
Section: Global Biogeochemical Cyclesmentioning
confidence: 99%
See 1 more Smart Citation